Histoplasmosis and kidney transplantation: case report - Pádua Netto, Marcus Vinícius de; Lima, Henrique Vieira de; Costa, Émerson Nunes; Borges, Ana Paula de Souza; Pádua Netto, Luiz Cláudio; Santos, Eduardo Moreira dos; Gomes, Alisson Augusto da Silva; Carvalho, Célio José Victal de; Ferreira, Marcelo Simão; Borges, Aércio Sebastião (Brazilian Journal of Transplantation, 2007)
This report describes a case of a 44-year-old white woman, who was on hemodialysis from 2001 to 2005, when she received a deceased renal transplant. Immediate postoperative immunosuppression consisted of oral tacrolimus, prednisone and mycofenolato mofetil (MMF), and by that time, her medication consisted of tacrolimus 3mg b.i.d, MMF 500mg b.i.d and prednisone 10mg qd, enalapril 20mg bid. Two years after transplantation, patient developed injury in the upper lip on the right, initially presenting spontaneous improvement, and no diagnosis was established at that moment. After two weeks, she returned to the hospital with the same injuries, now with involvement of the nasal wing and upper lip on the left, fever, cough and dysphonia. Chest radiograph revealed interstitial infiltrated in both lungs without mass. She was admitted in the hospital, and the pathologic evaluation of the nose and lung was performed, revealing Histoplama capsulatun. Confirmed the diagnosis, the treatment started with Itraconazole 400mg/dia. On the seventh hospitalization day, patient developed abdominal pain and distension, vomit, oliguria and hypotension, with worsening of the renal function. She evolved with severe hemodynamic instability and respiratory failure, the patient was sent to the Intensive Care Unit and evolved to death after 24 hours. Histoplasmosis is an important post-transplant complication, which must always be remembered, since Brazil is an endemic area, and due to the tragic evolution that the pathology can present.